The development of H class insulation system for variable speed low voltage random-wound stators - Risla, Jere (My University, 2021)
The topic of the thesis was from the Research and Development department of ABB oy, IEC LV Motors, Vaasa. The task was to develop two options for electrical insulation systems for low voltage variable speed motors with random-wound stators for at least thermal class H. The goals were good electrical and thermal qualities, cost savings and prospects of utilizing the electrical insulation materials tested in this work also in certain e-mobility stator insulation systems. High performance and reliability of the insulation systems is essential. Overstressing the insulation causes its accelerated aging, which can occur from such stresses as electric or thermal. The research in this work was done by selecting a group of electrical insulation materials and first studying them with material tests according to standards. The studied materials were electrical insulation laminates for slot and phase insulation. Based on the results of the material tests, candidate insulation systems were designed, which were categorized in two groups based on expected good electrical and thermal performance and based on cost savings potential. The systems were then realized by manufacturing a set of stators for testing purposes. The insulation systems were tested with a partial discharge test. The test results were evaluated in terms of partial discharge inception voltages and were compared to relevant standards and to a reference H class variable speed drive intended stator insulation system. Other ways of evaluation were also used for the insulation systems, namely a thermal class evaluation based on literature, considering the comments from production, and considering the insulation materials for e-mobility with separate partial discharge measurements for this purpose. The suggestion at the end of this work was not two insulation systems as originally planned, but one system. This is because the cost-effective system was not as promising as expected. The flexible electrical insulation in the cost-effective system was considered for the existing standard H class system. The proposed system for variable speed operation was the high-end system. Based on the tests and evaluations, the suggested new variable speed drive insulation system increased the phase-to-phase partial discharge inception voltages compared to the reference system and could have materials for an improved thermal class. The phase and slot insulations of this system were also considered to be tried in the e-mobility application discussed in appendixes. Lastly, by not including one specific type of insulation material and using less material in the new variable speed drive system, cost saving potential existed also in this system with respect to the reference H class variable speed drive system. As further studies were the thermal properties of the proposed system named as an example.

Diplomityön aihe oli ABB oy, IEC LV Motorsin Vaasan tuotekehitysosastolta. Tarkoituksena oli kehittää kaksi eristejärjestelmävaihtoehtoa taajuusmuuttajakäyttöön pyörölankakäämityille pienjännitemoottorin staattoreille vähintään H-lämpöluokkaan. Tavoitteina olivat hyvät jännitteen ja lämmön keston ominaisuudet, kustannussäästöt sekä mahdollisuus soveltaa tässä työssä testattuja eristemateriaaleja myös tiettyjen sähköisten ajoneuvojen staattoreiden eristejärjestelmissä. Eristejärjestelmien korkea suorituskyky ja luotettavuus ovat keskeisiä, sillä eristyksen liika rasittaminen johtaa sen nopeutettuun vanhenemiseen, joka voi seurata esimerkiksi jännitteen tai lämmön aiheuttamasta rasituksesta. Tutkimus toteutettiin valitsemalla joukko sähköeristeitä ja tutkimalla niitä ensin standardien mukaisilla materiaalitesteillä. Tarkastellut eristemateriaalit olivat ura- ja vaihe-eristykseen käytettäviä eristelaminaatteja. Materiaalitestien tulosten perusteella suunniteltiin eristejärjestelmät, jotka jaettiin kahteen ryhmään odotetun korkean sähköisen suorituskyvyn ja lämmön keston perusteella sekä kustannussäästöpotentiaalin perusteella. Järjestelmät toteutettiin valmistamalla tuotannossa staattorit tutkimusta varten. Staattoreiden eristejärjestelmät testattiin osittaispurkausmittauksella, jonka tulokset arvioitiin verraten osittaispurkausten syttymisjännitteitä standardeihin ja H-lämpöluokan taajuusmuuttajakäytön verrokkistaattoriin. Esitettyjä eristejärjestelmiä arvioitiin myös kirjallisesti lämpöluokkaan liittyviltä ominaisuuksiltaan ja tuotannon kommenttien perusteella sekä pohdittiin materiaalien soveltuvuutta sähköisiin ajoneuvoihin erillisen osittaispurkausmittauksen myötä. Työn lopputuloksena ehdotettiin yhtä valmista eristejärjestelmää eikä kahta järjestelmää kuten aluksi oli tarkoitus, sillä järjestelmä, jonka pääpaino oli kustannussäästöissä ei ollut testeissä täysin toivotunlainen. Tästä huolimatta tämän järjestelmän materiaaleja voitiin harkita nykyiseen H-luokan standardijärjestelmään. Työn lopussa ehdotettu taajuusmuuttajakäyttöön tarkoitettu järjestelmä oli siis korkean suorituskyvyn versio. Testeihin ja arviointeihin perustuen ehdotetun järjestelmän osittaispurkausten syttymisjännite oli nyt entistä korkeampi vaiheiden välillä verrokkijärjestelmään verrattuna. Lisäksi ehdotettu järjestelmä sisälsi eristemateriaaleja, jotka voisivat mahdollistaa korkeamman lämpöluokan. Järjestelmän vaihe- ja uraeristettä voitiin harkita liitteissä käsitellyn sähköajoneuvon staattoriin. Koska yhtä tiettyä eristemateriaalia ei käytetty ja eristeen määrä väheni, kustannusten pitäisi olla alhaisempia kuin verrokkina olleen H-luokan taajuusmuuttajakäytön järjestelmällä. Jatkossa olisi hyvä tutkia lisää ehdotetun järjestelmän lämmönkestoa.
Keywords: insulation; electrical engineering; electric motors; electric machines; standards; laminated materials; fi=Sähkötekniikka|en=Electrical Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|